Aneurysmal Fibrous Histiocytoma:: A Rare Variant - T M, Sheethal Shanibi; V, Vineetha K; Sahabudheen, A M; Rao, Vidyadhar (Annals of Pathology and Laboratory Medicine, 2020)
Aneurysmal fibrous histiocytoma (AFH) is a rare variant of benign fibrous histiocytoma. This tumor accounts for less than 2% of all fibrous histiocytomas, 1.7% of all cutaneous fibrous histiocytoma and it is typically known to occur in the extremities of middle-aged patients. A 23 year old male presented with slow growing, pigmented, nodular lesion on the left leg for the past 2 years. The swelling was initially non-tender, but there was a sudden increase in size associated with pain for the past 2 months. With a clinical suspicion of malignant melanoma an excision biopsy was performed and further evaluated by histopathology. The skin covered pigment lesion measuring 1.5x0.8x0.5cm showed fibrohistiocytic cellular proliferations containing blood filled spaces lacking endothelium on microscopy. Ancillary testing with bleaching, perls prussion blue reaction demonstrated the pigment as hemosiderin. Subsequently the lesion was negative for CD34 and positive for Factor XIIIA. Based on the histomorphology, ancillary testing and IHC, the diagnosis of Aneurysmal fibrous histiocytoma was made. Aneurysmal fibrous histiocytoma can be a challenging diagnostic entity due to its close clinical resemblance to melanoma and hemngioma. Although the pathogenesis is unclear, it is believed to be caused by extravasation of erythrocytes from capillaries leading to formation of the cystic blood spaces.